Effects of harvesting time on the storage quality of fresh-cut iceberg lettuce (The Philippine Journal of Crop Science, 2010)
This experiment was carried out to investigate the effect of harvesting raw materials at different time of the day (early morning and midday) on the storage of fresh-cut iceberg lettuce. Lettuces were harvested at early morning (06:00) and noon (12:00) in different seasons (January in winter and March in spring). The field temperature and relative humidity (RH) during harvesting ranged 7.2-13.8 Celsius and 65-76%, respectively in January while 10.4-24.8 C and 49-66%, respectively in March. Iceberg lettuce leaves were cut into 3 x 3 cm slices and washed in 100 uL L-1 chlorine solution; packaged with 80 mm nylon/polyethylene film and stored at 5 C for 12 days. No significant difference was found in headspace gas composition and quality in fresh-cut iceberg lettuce from raw materials harvested either at 6 AM or noon in January. However, in March, lettuce as fresh-cut harvested at noon with 49% RH and 24.8 C temperature showed lower CO2 concentration and off-odor index score as compared with samples harvested at 6 AM with 66% RH and 10.4 C. The results indicate that better quality of fresh-cut iceberg lettuce can be achieved when harvested under low humidity in spring season.